A Case Study of Gamma Waves in a Woman with Recent Psychotic Symptoms. (2nd April 2016) - Reeves, Roy R.
ABSTRACT: Reported here is the case of a 41-year-old female who developed paranoia and delusions. Physical examination, laboratory studies, and neuroimaging were unremarkable. She was diagnosed with schizophrenia and treated with risperidone, ultimately at a dose of 3 mg daily, with improvement. Her EEG showed bursts of 30–40 Hz gamma activity in the frontal regions, a finding sometimes noted on the resting EEGs of patients with schizophrenia. This report discusses gamma activity as well as other EEG abnormalities that may occur on the resting EEG of patients with schizophrenia. Additionally discussed is recent research suggesting that 35–45 Hz gamma activity associated with active information processing and cognition may be decreased in patients with schizophrenia compared to normal individuals. The role of gamma activity, both in the resting state and during cognitive activity, could be an area of importance for future research in schizophrenia and possibly other disorders.